SPECIAL METHODS AND PROCEDURES OF AUDIT REPORTS, WHICH ARE PREPARED BY THE SPECIALIZED ORGANIZATION - VERA Dvoretskaya (Учёт. Анализ. Аудит)
The article describes the main problems that the auditor faces with in the course of validation of the accounting (financial) statements, if a specialized organization maintains accounting records and/or prepares the accounting (financial) statements. The inclusion of additional sections and procedures, which are associated with the need to take into account the specific features of the economic entity for the preparation of the accounting (financial) statements in the validation program, will allow to reduce the auditor’s risk. As a result of this work there were suggested some special additional auditing procedures: the testing of the significant terms and conditions of thecontract with the specialized organization, the assessment of the internal control system of a specialized auditing organization, the assessment of the level of professional background of the persons responsible for accounting, preparation and submission of accounting (financial) statements. It was also suggested to add supplementary information in the letter informing about auditing, as well as the regulations of the auditing organization “Providing access to service a new client and prolongation of the cooperation with the existing customers”.